Association between endocrine disrupting chemicals exposure and diabetic kidney disease in adults: A national cross-sectional NHANES study - Xinru Li; Xiaoang Ye; Luhuan Xu; Hongyu Chen (Ecotoxicology and Environmental Safety)
Background: Diabetic kidney disease (DKD) is a global public health concern. Environmental factors are increasingly recognized as significant risk factors that cannot be overlooked, and certain environmental pollutants exhibit endocrine-disrupting properties. Previous research on the association between endocrine-disrupting chemicals (EDCs) and DKD has been notably limited. Methods: This study investigated the association between exposure to 25 EDC metabolites and DKD in 1421 U.S. adults from the 2015–2018 National Health and Nutrition Examination Survey (NHANES). We used logistic regression, restricted cubic spline regression, weighted quantile sum (WQS) regression, and bayesian kernel machine regression (BKMR) models to assess the association between individual and co-exposure to multiple EDCs and DKD. Subgroup analyses and interaction tests were performed to investigate whether this association was stable across the population. Additionally, mediation analysis was used to explore the mediating role of serum globulins in the association between Pb exposure and DKD. Results: In logistic regression models, N-Acetyl-S-(2-hydroxypropyl)-L-cysteine (2HPMA), N-Acetyl-S-(4-hydroxy-2-butenyl)-L-cysteine (MHBMA3), Phenylglyoxylic acid (PGA), and lead (Pb) were significantly positively associated with diabetes. Restricted cubic spline (RCS) analyses also revealed significant non-linear positive associations between 2HPMA, MHBMA3, and DKD. Perfluorohexane sulfonic acid (PFHxS), n-perfluorooctanoic acid (n-PFOA), n-perfluorooctane sulfonic acid (n-PFOS), and Perfluoromethylheptane sulfonic acid isomers (Sm-PFOS) were significantly negatively associated with DKD. Furthermore, co-exposure to metals and metalloid was positively associated with DKD in both the WQS regression and the BKMR models, with Pb as the primary contributing factor. Mediation analysis showed that globulin mediated the association between Pb exposure and DKD, with a mediation proportion of 7.25 % (P = 0.046). Co-exposure to perfluoroalkyl and polyfluoroalkyl substances (PFASs) was negatively correlated with DKD, and subgroup analyses revealed that this correlation was more pronounced in the obese group (BMI ≥30 kg/m²). The BKMR analysis revealed potential interactions among various chemical compounds, such as N-Acetyl-S-(2-hydroxypropyl)-L-cysteine (2HPMA), 2-Methylhippuric acid (2MHA), N-Acetyl-S-(4-hydroxy-2-methyl-2-butenyl)-L-cysteine (IPM3), mercury (Hg), and cadmium (Cd), in a model simulating co-exposure to metals and metalloid, as well as to volatile organic compound metabolites (mVOCs). Conclusion: The findings suggest an association between individual or co-exposure to EDC metabolites and DKD, providing valid evidence for DKD prevention from the perspective of EDCs exposure. However, more prospective studies are needed to elucidate the potential mechanisms underlying these findings.